Linguistic Search by C.S. Boosting Optimization Algorithm - B Shashirekha, G Akhila, NM.Deepika, T Sahithi, V.Sudheshna, B Padmaja (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The internet data developed incrementally and gathered as unstructured information like textual documents, pictures, videos and sound content etc. This information material is created daily from several social networking resources such as sites, Twitter news posts, community websites, even Face book, etc. Information sharing is occurring across programs of various businesses like healthcare, education, societal sites, and army forums, community-based Q.A. sessions, client attention, etc. Information retrieval methods are used for getting relevant data from acollection of tools to resolve consumer requirements anywhere at any moment. Users expect precise responses with a brief response time instead of a listing of files during internet searches. Data sources show up in various formats, and thus it's pretty tricky to recover data without processing for simple recovery. The construction and arrangement of information in a predetermined format are required, and it's accomplished by data preprocessing and clustering from its comparable classes. In this paper, a cuckoo searchoptimization algorithmis proposed to reduce the search space and time complexity. An experimental result demonstrates that the algorithm generated greater accuracy in contrast to state-of-art procedures.